Sex difference in age-related changes in knee extensor strength and power production during a 10-times-repeated sit-to-stand task in Japanese elderly. Issue 1 (December 2015) - Yanagawa, Naoko; Shimomitsu, Teruichi; Kawanishi, Masashi; Fukunaga, Tetsuo; Kanehisa, Hiroaki
Abstract Background For middle-aged and elderly women, age-related decline in an index representing power production during STS task (STS-PI), calculated by using an equation reported previously, has been shown to be greater than that in the force generation capability of lower extremity. Whether this is specific to women remains unclear. This study examined how the age-related changes in knee extensor strength and power production during STS differ between Japanese men and women aged 65 years or older. Methods The time taken for a 10-times-repeated STS test (STS time) and force developed during maximal voluntary isometric knee extension (KE-F) were determined in Japanese younger-old (262 men and 285 women) aged 65–74 years and older-old (96 men and 89 women) aged 75–90 years. STS-PI was calculated using the following equation: STS-PI = (body height − 0.4) × body mass × 10/STS time. Results KE-F and STS-PI were significantly greater in the younger-old than in the older-old group (p  < 0.0001) and in men than in women (p  < 0.0001). STS-PI and KE-F, expressed as the percentages of the mean value of the corresponding variable for the younger-old group (%STS-PI and %KE-F, respectively), were negatively correlated to chronological age in both men (r  = −0.386 andr  = −0.269, respectively, p  < 0.0001) and women (r  = −0.504 andr  = −0.294, respectively, p  < 0.0001). Regression slopes in the relationship between age and %KE-F were not significantly different between men (−1.521) and women (−1.618). However, regression slope in the relationship between age and %STS-PI was significantly steeper in women (−3.108) than in men (−2.170) (p  < 0.05). In OOG, %KE-F had no significant effect of sex, but %STS-PI was significantly lower in women than in men (p  < 0.001). Conclusions In Japanese men and women aged 65 years or over, age-related loss in power production during STS is steeper in women than in men, with greater magnitude than that in knee extensor strength. This suggests a higher priority of improving power generation capability during whole-body movement such as STS in older women than in older men.